Pengembangan Aplikasi Penyesuai Playlist Musik dengan Konsep Geofencing menggunakan Spotify API Berbasis Android - Fachri Rachmanda; Agi Putra Kharisma; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Listening to music is one of the biggest uses of smartphones, because certain music is considered to be able to affect mood and mind in carrying out various activities. One of the most popular music listening service providers is Spotify, which currently does not provide location-based music playback services. Therefore an application development for Android-based smartphones is conducted to adjust the playback of the type of music from Spotify based on the user's activities with the location as a reference for the adjustment. This application applies the concept of geofencing which is implemented with the Java programming language on the Android SDK (Software Development Kit). The results of functional testing with black box testing show that the function of this application has fulfilled the main functional needs of the system in adjusting the playlist and complementary functions that support the main function. In the usability test using the SUS (System Usability Scale) method involving ten respondents obtained 60.75% results or included in the category of